MODERN TREATMENT OF GASTRIC CANCER RELEVANCE OF THE PROBLEM (World Bulletin of Social Sciences, 2024)
Cancer is a malignant tumour that has autonomous and progressive growth. In foreign medical literature, the term is often used to refer to all malignant tumours, regardless of their origin or tissue composition. Each tumour may have its own characteristics and propensity to form metastases, so a cancerous tumour behaves differently in the body [1]. Gastric cancer is the third leading cause of cancer-related mortality worldwide. More than 95% of gastric cancers are adenocarcinomas, which are usually classified based on anatomical localisation and histological type. Gastric cancer usually has a poor prognosis as it is often diagnosed at an advanced stage [2]. Any cell in the body can become malignant. And the treatment methods that can fight cancer will depend on its characteristics. Cells of almost all our organs are different from each other, moreover, cells of one organ can also be different. Therefore, speaking about stomach cancer, it should be noted that this is a group of diseases that are caused by different reasons, proceed in different ways and require different treatment approach